Peacekeeping and Development in Fragile States : Micro-Level Evidence from Liberia - Mvukiyehe, Eric; Samii, Cyrus (World Bank, Washington, DC, 2018)
Using surveys and administrative data from post-war Liberia, the hypothesis that peacekeeping deployments build peace "from the bottom up" through contributions to local security and local economic and social vitality was tested. The hypothesis reflects official thinking about how peacekeeping works via "peacebuilding." A quasi-experiment was created by applying coarsened exact matching to administrative data used in mission planning, identifying sets of communities that were similarly likely to receive peacekeeping bases. The analysis finds nothing to support claims that deployments increase local security and finds only modest effects on economic or social vitality. Nongovernmental organizations tend to work in areas where deployments are not present, contrary to the hypothesis. Thus, it is less likely that peacekeepers build peace from the bottom up, leaving mechanisms such as signaling and deterrence at the level of leaders as worthy of more attention. For policy, peacekeeping missions should reevaluate their methods for providing local security.